Isolation and characterization of a Solanum tuberosum subtilisin-like protein with caspase-3 activity (StSBTc-3) - Fernandez, María Belén (2015)
Plant proteases with caspase-like enzymatic activity have been widely studied during the last decade. Previously, we have reported the presence and induction of caspase-3 like activity in the apoplast of potato leaves during Solanum tuberosum- Phytophthora infestans interaction. In this work we have purified and identified a potato extracellular protease with caspase-3 like enzymatic activity from potato leaves infected with P. infestans. Results obtained from the size exclusion chromatography show that the isolated protease is a monomeric enzyme with an estimated molecular weight of 70 kDa approximately. Purified protease was analyzed by MALDI-TOF MS, showing a 100% of sequence identity with the deduced amino acid sequence of a putative subtilisin-like protease from S. tuberosum (Solgenomics protein ID: PGSC0003DMP400018521). For this reason the isolated protease was named as StSBTc-3. This report constitutes the first evidence of isolation and identification of a plant subtilisin-like protease with caspase-3 like enzymatic activity. In order to elucidate the possible function of StSBTc-3 during plant pathogen interaction, we demonstrate that like animal caspase-3, StSBTc-3 is able to produce in vitro cytoplasm shrinkage in plant cells and to induce plant cell death. This result suggest that, StSBTc-3 could exert a caspase executer function during potato- P. infestans interaction, resulting in the restriction of the pathogen spread during plantepathogen interaction.